2020
DOI: 10.3390/agronomy10040481
|View full text |Cite
|
Sign up to set email alerts
|

Teosinte (Dioon mejiae) Flour: Nutritional and Physicochemical Characterization of the Seed Flour of the Living Fossil in Honduras

Abstract: Teosinte (Dioon mejiae) is a dioecious tree native to Honduras, whose seeds are used to make flour for the preparation of traditional foods and beverages. The objective was to evaluate the nutritional and physicochemical composition of teosinte flour for the first time. Using diverse techniques, teosinte flour was found to be a high-calorie food rich in total carbohydrates and mainly composed of starch, with an amylopectin:amylose ratio of 2:1 and a concentration of resistant starch greater than 50%. Its prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 30 publications
0
17
2
Order By: Relevance
“…Kadan et al [26] found that rice bread had a lower specific volume than wheat bread; in our study the addition of TF to BRF resulted in a greater specific volume. According to Bastias-Montes et al [11], protein and total starch contents were 9.67 ± 0.08% and 67.90 ± 0.68% in teosinte The crumb color pattern was different from the crust pattern. The lightness of the bread crumb (Figure 2F) was lowest with the use of TF alone, which might be due to the natural, brownish pigments in the seeds [33].…”
Section: Bread Characteristicsmentioning
confidence: 95%
See 2 more Smart Citations
“…Kadan et al [26] found that rice bread had a lower specific volume than wheat bread; in our study the addition of TF to BRF resulted in a greater specific volume. According to Bastias-Montes et al [11], protein and total starch contents were 9.67 ± 0.08% and 67.90 ± 0.68% in teosinte The crumb color pattern was different from the crust pattern. The lightness of the bread crumb (Figure 2F) was lowest with the use of TF alone, which might be due to the natural, brownish pigments in the seeds [33].…”
Section: Bread Characteristicsmentioning
confidence: 95%
“…Kadan et al [26] found that rice bread had a lower specific volume than wheat bread; in our study the addition of TF to BRF resulted in a greater specific volume. According to Bastias-Montes et al [11], protein and total starch contents were 9.67 ± 0.08% and 67.90 ± 0.68% in teosinte flour, and Aleman et al [27] found that high-protein brown rice flour had 12.2 ± 0.14% protein and 65.4 ± 0.5% starch, while high-protein white rice flour had 10.23 ± 0.26% protein and 75.15 ± 0.20% starch [28]. The specific volume is directly related to water absorption of the network, which affects bread quality, and bread with greater starch content tended to have a greater specific volume [29].…”
Section: Bread Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These alternative ingredients offer the potential to increase protein content and beneficial dietary fiber and provide a range of essential vitamins and minerals. The inclusion of such ingredients aligns with the growing demand for healthier gluten-free snack options and can contribute to diversifying the cookie market with innovative and nutritionally enriched offerings [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Teosinte holds a significant cultural and historical importance to Honduras, where it has been utilized since ancient times and is widely distributed in the northeastern regions [ 6 ]. This cycad plant serves a dual purpose in the region, serving as a vital food source for over 30,000 Hondurans and playing a role in ceremonial ornamentation across numerous communities throughout the country [ 7 ].…”
Section: Introductionmentioning
confidence: 99%